0001 Activation of Nociceptin/Orphanin-FQ Peptide (NOP) Receptors Produces an Increase in Non-REM Sleep in Rats and Constitutes a Novel and Attractive Target for the Treatment of Insomnia. (27th May 2020) - Whiteside, G T; Hummel, M; Knappenberger, T; Hiroyama, S; Itoh, T; Takai, N; Kyle, D J
Abstract: Introduction: Treatments for insomnia have targeted GABA, histamine, serotonin, melatonin and orexin receptors. The nociceptin/orphanin-FQ peptide (NOP) receptor is widely expressed in the nervous system. High doses of NOP agonists administered systemically or locally into the CNS can result in sedation, however, the utility of targeting this receptor to treat insomnia has not been fully described. Methods: V117957 is a recently described investigational oral, potent and selective NOP receptor partial agonist. We determined the brain Kp in whole brain and multiple sub-regions (50mg/kg) and receptor occupancy in the hypothalamus (30, 300mg/kg) via in vivo displacement using [ 3 H]-NOP-1A. EEG/EMG were determined in rats chronically implanted with electrodes (cortex and dorsal neck muscle) and recorded via telemetry following dosing (3, 30, 300mg/kg); sleep stage was determined from visual analysis of EEG level. Sleep parameters were also assessed in NOP receptor knock-out rats (300mg/kg). The side-effect profile for V117957 was determined by functional observation battery, whole-body plethysmography, Morris water maze (MWM) (up to 600mg/kg) and conditioned place preference (CPP) assay (up to 300mg/kg). Results: V117957 displayed limited distribution into the CNS but achieved a high level of receptor occupancy (75% at 30mg/kg). Administration of V117957 produced dose-dependent and statistically significant increases in non-REM sleep with a minimally efficacious dose of 30mg/kg; a coincident dose-dependent and statistically significant decrease in wakefulness and a non-dose-dependent effect on REM sleep occurred. These changes were not seen in knock-out animals demonstrating effects are via NOP receptors. At doses higher than those that increased non-REM sleep, V117957 had no effects in a functional observational battery, did not affect escape latency in MWM or produce CPP; additionally, V117957 did not affect respiratory parameters. Conclusion: We conclude that activation of NOP receptors decreases wakefulness and increases non-REM sleep in rats with an improved preclinical profile compared to historical profiles of current treatments and, therefore, may represent a novel and attractive target for the treatment of insomnia. Support: Funded by Shionogi and Imbrium Therapeutics, a subsidiary of Purdue Pharma L.P.